Dairy Enterprise – 100 Lactating Cows (Freestall) - Dhuyvetter, Kevin C.; Harner III, Joseph P.; Brouk, Micheal (My University, 2014)
This publication examines the cost and returns for a dairy operation with 100 lactating cows in a freestall system.
MF272_2014_04
Keywords: MF272; Livestock; Economics; MF